Diffusion processes during drying of solids - Shukla, K.N (World Scientific, 1990)
The monograph presents a detailed mathematical examination of the generalised laws of diffusion in capillary porous solids as applicable to particular geometric situations of interest in the technology of drying. The novelty of the monograph is to present the result in dimensionless form under general type of boundary conditions. Many important results are presented graphically. The integral transform technique is used throughout the work and a host of useful information of the technique is included in the appendix. Research scientists and practising engineers in the areas of applied mathematics, materials and energy will find it a very useful monograph.